Assessment of bowel and anal sphincter function after neoadjuvant chemoradiotherapy in locally advanced rectal cancer. Issue 2 (March 2018) - Rosa, Consuelo; Di Tommaso, Monica; Caravatta, Luciana; Vinciguerra, Annamaria; Augurio, Antonietta; Perrotti, Francesca; Allajbej, Albina; Regoli, Marco; Zecca, Isaia AL; Di Nicola, Marta; Genovesi, Domenico
Purpose: To report long-term effects on anorectal function and bowel disorders and late toxicity rate of preoperative chemoradiotherapy in patients with locally advanced rectal cancer. Methods: Between 2000 and 2016, 201 patients treated with different neoadjuvant schedules of chemotherapy and radiotherapy doses were retrospectively analyzed. The Memorial Sloan–Kettering Cancer Center score was used for the evaluation of anal sphincter function. Results: The median follow-up time was 68 months (interquartile range 35–113 months). Radical resection was performed in 188 (93.5%) patients with a pathologic complete response rate of 26.4%. Overall sphincter function resulted excellent in 105 (52.2%) patients, good in 13 (6.5%), fair in 10 (5.0%), and poor (incontinence) in 40 (19.9%), with a persistent stoma rate of 16.4%. A further evaluation on 194 patients showed an improvement of sphincter function after 2 years in 11.9% of them. Seventy-three patients presenting stoma or poor sphincter function were re-evaluated for quality of life (QoL) indexes. Twenty-one (29%), 19 (26%), and 24 (33%) of them declared some variations concerning well-being, fatigue, and ability to perform daily activities. The 5-year overall survival, disease-free survival, and local recurrence rates were 88.0% ± 2.6%, 86.3% ± 2.5%, and 94.6% ± 1.9%, respectively. Conclusions: In our study, neoadjuvant chemoradiotherapy was associated with good results in terms of sphincter function, late toxicities, and QoL indexes. A routine use of assessment scales could contribute to a better selection of patients with increased risk of developing functional disorders who could benefit from neoadjuvant therapy.